2019
DOI: 10.3390/pr7120873
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Triangular Silver Nanoplates by Gelatin–Chitosan Mixture and the Influence of Their Shape on Antibacterial Activity

Abstract: Triangular silver nanoplates were prepared by using the seeding growth approach with the presence of citrate-stabilized silver seeds and a mixture of gelatin-chitosan as the protecting agent. By understanding the critical role of reaction components, the synthesis process was improved to prepare the triangular nanoplates with high yield and efficiency. Different morphologies of silver nanostructures, such as triangular nanoplates, hexagonal nanoprisms, or nanodisks, can be obtained by changing experimental par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Being able to penetrate the bacteria membrane with three edges, Pal et al [ 36 ] suggested, through TEM images, that truncated triangular nanoplates were the most aggressive, leading to the highest capacity to kill bacteria [ 36 ]. This theory was also analyzed by Vo et al in 2019 [ 37 ]; by comparing the spherical and the triangular shape of Ag NPs, a higher bactericidal effect was associated with the triangular shape. Previous studies attributed this result to the crystallographic structure of Ag; the (111) facet found in a higher quantity in triangular shape can interact easier with bacteria membrane and can produce necrosis faster [ 36 , 37 , 38 ].…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 74%
See 1 more Smart Citation
“…Being able to penetrate the bacteria membrane with three edges, Pal et al [ 36 ] suggested, through TEM images, that truncated triangular nanoplates were the most aggressive, leading to the highest capacity to kill bacteria [ 36 ]. This theory was also analyzed by Vo et al in 2019 [ 37 ]; by comparing the spherical and the triangular shape of Ag NPs, a higher bactericidal effect was associated with the triangular shape. Previous studies attributed this result to the crystallographic structure of Ag; the (111) facet found in a higher quantity in triangular shape can interact easier with bacteria membrane and can produce necrosis faster [ 36 , 37 , 38 ].…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 74%
“…This theory was also analyzed by Vo et al in 2019 [ 37 ]; by comparing the spherical and the triangular shape of Ag NPs, a higher bactericidal effect was associated with the triangular shape. Previous studies attributed this result to the crystallographic structure of Ag; the (111) facet found in a higher quantity in triangular shape can interact easier with bacteria membrane and can produce necrosis faster [ 36 , 37 , 38 ]. Even if in the case of bacteria species, sharp nanoparticles exhibit stronger bactericidal effects, for a faster regeneration of the lesions and for a proper distribution in the body fluids, spherical nanoparticles are also preferred in most applications, being the most studied nanoparticles.…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 74%
“…TSNPs have been reported to exhibit higher antimicrobial activity, attributed to a rate of Ag + ion release five times larger, compared to spherical NPs. As Ag + ion release is caused by oxidation, the increased ion release of TSNPs is a consequence of their sharp edges and corners, which make them more susceptible to oxidation [ 13 , 14 , 15 , 16 , 17 ]. It is also recognised that larger surface-to-volume ratio possessed by smaller NPs compared to larger ones allows smaller particles to release more Ag + ions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the available specialized data (PDF no. 00-004-0783), these peaks correspond to (1 1 1), (2 0 0), (2 2 0) and (3 1 1) diffraction planes of silver crystals with face-centered cubic (fcc) lattice[52,53]. By indicating the high purity and crystalline nature of silver-based sample and by showing its characteristic fcc crystallographic lattice, the XRD pattern confirms that metallic silver represents the sole crystalline phase of the obtained powder.…”
mentioning
confidence: 61%